Pulmonary adenocarcinoma with liver metastasis in a cat: Clinical, radiological, anatomopathological and cytopathological report - Cardoso, João Felipe Rito; Menezes, Roberta Salim; Moura, Mariana; Almeida, Elan Cardozo Paes de (Pubvet, 2021)
The incidence of primary lung cancer in cats has been increasing due to many factors, including greater contact with air pollutants. However, the diagnosis is made late in most cases, making it impossible to adopt efficient therapies. In this sense, the present report presents the clinical, radiological, anatomopathological and cytopathological comparison of a pulmonary adenocarcinoma with liver metastasis, aiming to provide useful information to the clinician and early screening detection, as well as using low cost, easy-to-perform, low-invasive and reliable tools. The present report shows symptoms of progressive weight loss, anorexia, lethargy and mild dyspnea, associated with the presence of a circumscribed radiopaque mass in the right caudal pulmonary lobe and diffuse interstitial pulmonary opacification at X-ray. At necropsy, presence of effusions in the thoracic and abdominal cavities and tumor masses in lung and liver. The cytopathological examination suggested a diagnosis of carcinoma, being corroborated by the anatomopathological diagnosis of grade 2 mixed pulmonary adenocarcinomas, with liver metastasis. The comparisons made in this study suggest that radiological examination is essential for the diagnosis and clinical staging of lung neoplasms, while histopathology is the gold criterion for definitive diagnosis and tumor classification. However, cytopathology is a quick, low-invasive and safe diagnostic tool for preliminary diagnosis and during surgical and necroscopic procedures when freezing histopathology or pathology laboratories are not accessible.
Keywords: Cat; citopatology; lung; neoplasia